2007
DOI: 10.1158/1541-7786.mcr-06-0348
|View full text |Cite|
|
Sign up to set email alerts
|

Ursolic Acid Inhibits STAT3 Activation Pathway Leading to Suppression of Proliferation and Chemosensitization of Human Multiple Myeloma Cells

Abstract: The activation of signal transducers and activators of transcription 3 (STAT3) has been linked with the proliferation of a variety of human cancer cells, including multiple myeloma. Agents that can suppress STAT3 activation have potential for prevention and treatment of cancer. In the present report, we tested an agent, ursolic acid, found in basil, apples, prunes, and cranberries, for its ability to suppress STAT3 activation. We found that ursolic acid, a pentacyclic triterpenoid, inhibited both constitutive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
139
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 218 publications
(146 citation statements)
references
References 71 publications
4
139
0
3
Order By: Relevance
“…and Prunell avulgaris L. (Cheung et al, 2006;Cheung and Zhang, 2008). It exhibits a broad range of pharmacological effects such as anti-inflammatory, antiviral, antioxidant, and hepatoprotective activities (Feuillolay et al, 2016;Kashyap et al, 2016;Siegel et al, 2016), and has proven to be effective in treating various types of cancers including CRC (Pathak et al, 2007;Prasad et al, 2012;Lin et al, 2013;Kadioglu and Efferth, 2015). Several mechanisms by which UA acts as a chemosensitizer have been proposed, such as pro-apoptosis (Meng et al, 2015) and anti-angiogenesis (Lin et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…and Prunell avulgaris L. (Cheung et al, 2006;Cheung and Zhang, 2008). It exhibits a broad range of pharmacological effects such as anti-inflammatory, antiviral, antioxidant, and hepatoprotective activities (Feuillolay et al, 2016;Kashyap et al, 2016;Siegel et al, 2016), and has proven to be effective in treating various types of cancers including CRC (Pathak et al, 2007;Prasad et al, 2012;Lin et al, 2013;Kadioglu and Efferth, 2015). Several mechanisms by which UA acts as a chemosensitizer have been proposed, such as pro-apoptosis (Meng et al, 2015) and anti-angiogenesis (Lin et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Several mechanisms by which UA acts as a chemosensitizer have been proposed, such as pro-apoptosis (Meng et al, 2015) and anti-angiogenesis (Lin et al, 2013). In addition, UA was found to be capable of affecting multiple signaling pathways including nuclear factor-κB (NF-κB) (Prasad et al, 2012), signal transducer and activator of transcription-3 (STAT3) (Pathak et al, 2007), and phosphatidylinositol 3-kinase/Akt/mammalian target of rapamycin (PI3K/Akt/mTOR) (Meng et al, 2015), among others. Here we showed that UA could sensitize colon cancer cells to both 5-fluorouracil (5-FU) and oxaliplatin under hypoxia by inhibiting the expressions of HIF-1α and its downstream effector MDR1.…”
Section: Introductionmentioning
confidence: 99%
“…Upon activation, STAT3 undergoes phosphorylation, homodimerization, nuclear translocation, and DNA binding, which subsequently leads to transcription of various target genes, such as cyclin D1, Bcl-2, Bcl-xL, matrix metalloproteinase 2 (MMP2), and VEGF, to regulate cell survival, angiogenesis, immune evasion, and inflammation in tumor microenvironment (8)(9)(10). Interfering with activated STAT3 signaling contributes to angiogenesis inhibition, tumor growth arrest, and metastasis suppression (11,12). Currently, STAT3 inhibitor, including natural compounds, peptide, peptidomimetic compounds, small molecules, and oligonucleotides, have been developed and are undergoing into clinical settings (4,13,14).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Pathak et al [33] clearly highlighted the potential of ursolic acid to modulate STAT3 signaling cascade in multiple myeloma. They found that ursolic acid can inhibit both constitutive and interleukin-6-inducible STAT3 activation in a dose-and time-dependent manner that correlated with the suppression of activation of upstream kinases (c-Src, Janusactivated kinase 1, Janus-activated kinase 2, and extracellular signal-regulated kinase 1/2).…”
Section: In Vitro Anticancer Effects Of Ursolic Acidmentioning
confidence: 99%
“…In a human chronic myelogenous leukemic cell line (K562), ursolic acid induced apoptosis via the up-regulation of PTEN gene expression, inhibited Akt kinase activity, altered the mitochondrial transmembrane potential and reduced the release of cytochrome c, enhanced the activity of caspases [42] as well as induced HL60 monocytic differentiation and up-regulated C/EBPb expression via activation of the ERK mitogen activated kinase pathway [43]. Ursolic acid is known to chemosensitize tumor cells to a number of chemotherapeutic agents [33,39]. In another study by Koh et al [44], ursolic acid was shown to radiosensitize DU145, CT26 and B16F10 cells and accelerated cell death, as evident by DNA fragmentation, changes in cellular redox status, mitochondrial dysfunction and modulation of apoptotic marker proteins.…”
Section: Biological Effects Referencesmentioning
confidence: 99%